ANALISIS NON PERFORMING LOAN DAN LOAN DEPOSIT TO RASIO TERHADAP KESEHATAN PD. BANK PERKREDITAN RAKYAT BKK KECAMATAN SEDAN KABUPATEN REMBANG - Muhammad Masruri (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
The main purpose of this study is to analyze the Non Performing Loan (NPL) and the Loan to Deposit Ratio (LDR) toward the health of PD. BPR BKK Kecamatan Sedan Rembang on 2000 to 2005. The hypotheses proposed was that according to its Non Performing Loan to Deposit Ratio, PD. BPR BKK Kecamatan Sedan Rembang, was unhealthy.The operational definition of this study consists of LDR (Loan to Deposit Ratio); that is the ability to obtain profit from the saving fund to be distributed in form of credit on PD. BPR BKK Kecamatan Sedan. The Bank productifity of fund, which has a high circulation, is cash. The target of this study is PD. BPR BKK Kecamatan Sedan Rembang, and the data used, is the data from 2000 2005.The technique of data collecting used in this study are; data in form of balance of sheet, financial statement, sum of productive tangible, and the sum of assets, from the year of 2000 2005. The study was conducted using quantitative method of data collecting to analyze the Loan to Deposit Ratio (LDR) and the Non Performing Loan (NPL) from 2000 2005.The result shows the Non Performing Loan (NPL) of PD. BPR BKK Kecamatan Sedan Kabupaten Rembang on 2000 was as much as 4.35 %, on 2001 was 3.06 %, on 2002 was 1.69 %. This means that the level oc credit was health. The Non Performing Loan (NPL) on 2003 was as much as 5.43 %, 2004 as 8.86 % and 2005 as 7.43 %. This can be assumed as unhealthy. While the Loan to Deposit Ratio (LDR) on 2000 as much as 118 %, 2001 as 114 %, 2002 as 80 %, 2003 as 33 %, 2004 as 71 %, and 2005 as 89.97 %.